Interrelationships between some urban mothers' nutrition behavior and nutrition education and their children's nutritional status in a depressed urban barangay a case study - Serrano, Noemi V.
The study was conducted primarily to determine the changes that might have occurred in the Nutrition Behavior (NB) of some urban mothers in Barangay 793, a depressed barangay in Sta. Ana, Manila from 1981 to 1988. Likewise, the changes in the Nutritional Status (NS) of their children then, 3-4 year olds and in 1988, aged 10-11 years were also determined. The factors that might have contributed to these changes were investigated. In the 1981 study, 39 mothers were interviewed on their NB. Also, the NS of their 3-4 year old preschoolers was studied. In the 2nd study, 9 of this mothers and their children were followed-up. In 1981, majority of the mothers had favorable nutrition knowledge and attitudes. Only 38 , however, had favorable nutrition practices. Of the preschoolers studied, 69 were either mildly undernourished. A hemoglobin level below 11 grams per 100 ml vanous blood was observed among 56 of the preschoolers. In 1981, there was no association found between the nutrition behavior of the mothers and the nutritional status of their children. In the 2nd study, it was found that 7 out of the 9 children remained well nourished after 7 years. 1 child who was previously normal by weight for height standards in 1981 became stunted. Another 1 remained stunted within the study period. It was observed that 5 of the 9 mothers had increased NB scores within the 7 year period. They had improved food preparation practices. Majority of the mothers still associated the illnesses of their children to sudden changes in weather, teething and other related reasons. Likewise, majority of them believed that breastfeeding was important to the child's health although they had some misconceptions about it. A relationship was found between the NB of the mothers and the NS of their children. Among the factors that might have contributed to the changes in the NB of the mothers were their education, husbands, the health center, and the physicians. The degree of influence on the NB differed among the cases. The results of the study will provide insights to nutrition planners and implementors on how to best plan the projects in the barangay for them to be effective. The NS of the children in 1981 and 1988, on the other hand, will serve as baseline information in monitoring their growth. It is vital that their growth be monitored, just like the rest of the children in the country, to prevent growth flatering. Furthermore, the results of the study will help identify possible entry points of nutrition and health related programs.